(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Type 2 diabetes, obesity, and cardiovascular disorders are among some of the lifestyle diseases that have spread throughout the world and are frequently connected to dietary choices. The potential of plant-based protein foods in preventing these illnesse